One-Pot Three-Component Access to Furan and Thiophene Derivatives - Bao, Ruipeng; Wang, Yao; Lin, Xinbo; Tan, Jinglin; Chen, Zhihua; Wang, Teng; Yu, Xinhong (Synlett, 2024)
The furan and thiophene skeleton structures are widely present in natural products and synthetic drugs, and display multiple bioactivities. An effective one-pot three-component reaction to access furan and thiophene derivatives from 2-bromo-5-(dichloromethyl)furan or -thiophene; cyanoacetate esters, cyanoacetamides, or malononitrile; and aliphatic secondary amines has been developed. The multicomponent reaction for the construction of new C–N and C–C bonds in one pot is simple, mild, and efficient, and the yield of the target product is as high as 96%.
Keywords: one-pot reaction; multicomponent reaction; furans; thiophenes; cascade reaction